Patri_Patter; Digital Portal with Adaptative Paradigms for the Recognition of Architectural Heritage - Manel Djazia TIAR (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
This summary deals with the proposal of an original method for architectural knowledge. The subject matter is architectural elements and their recognition as adaptable paradigms; interpretable and reusable. Our methodological scheme is heuristic and groups a morphogenetic protocol in synchronicity with a spatio-temporal process of narrative semiotics. It includes a morphological analysis of the genetic environment of the city under study (Blida), and the environment, the demonstration of adaptive use according to passive design and the evaluation of solar flux.The aim is to propose a design tool suitable for the sketching phase of sustainable projects. The result is the digital portal Patri_Patter, which corresponds to the ontological protocol (data, information, knowledge). Patri_Patter contains analytical, evaluative and interpretative sheets according to three levels of significant reading, namely referencing, adaptation and validation. They are available to actors who are committed to the added value of neighbourhoods and the improvement of social life.